Interleukin-6 in blood and bronchoalveolar lavage fluid of hospitalized children with community-acquired pneumonia - Zhang, Yun; Zheng, Wenyu; Ning, Haonan; Liu, Jing; Li, Fuhai; Ju, Xiuli (Frontiers in Pediatrics, 2022)
Background: Host biomarkers and cytokines predict disease severity in adults with community-acquired pneumonia (CAP). Accurate assessment of pathogens and disease severity is essential to clinical decision-making. There are few validated prognostic tools in blood and bronchoalveolar lavage for children with CAP, to assist with proper decision and management. Methods: We performed a retrospective study of 118 children under 18 years of age, hospitalized for CAP with bronchoalveolar lavage management within the first two days. The primary outcome was disease severity: mild(with no complications), moderate(with mild to moderate complications), and severe(with severe complications). Comparison and performance analysis of biomarkers and cytokines in blood or bronchoalveolar lavage fluid(BALF) across different severity categories/different pathogens were undergone. Results: Analysis of 118 CAP cases revealed significant differences in BALF IL-6(p=0.000), CRP(p=0.001), and ESR(p=0.004) levels across different severity categories, while BALF IL-6 was indicated the best at discriminating mild from moderate to severe cases with highest AUC(0.847, 95% CI: 0.748-0.946), fair sensitivity(0.839) and specificity(0.450), and severe from non-severe cases with highest AUC(0.847), sensitivity(0.917) and specificity(0.725). ALL biomarkers and cytokines had no significant difference across different pathogen categories(p>0.05), while BALF IL-6(p=0.000), blood ANC(p=0.028), and ESR(p=0.024) were obviously different in comparison to single mycoplasma pneumoniae-, bacteria- or virus-positive group versus non-group. Blood CRP(r=0.683, p=0.000) and ESR(r=0.512, p=0.000) revealed significant correlation with hospitalization course(HC). Among all the BALF cytokines, only BALF IL-6 showed a significant difference(p=0.004, p<0.01) across different severity categories, with good performance for predicting CAP severity in hospitalized children (AUC=0.875, P=0.004). Blood IL-6 and BALF IL-6 had no significant correlation, in addition, BALF IL6 was better at predicting CAP severity in hospitalized children(AUC=0.851, p=0.011, p<0.05) than blood IL-6. Conclusions: BALF IL-6 and blood CRP, ESR may have the ability for discriminating disease severity in hospitalized children with CAP, whereas WBC count and ANC have limited ability. No biomarkers or cytokines seemed to have the ability for pathogen category predicting, while BALF IL-6, blood ANC and ESR may assist in the diagnosis of single mycoplasma pneumoniae, bacteria, and virus infection respectively.